Pemberdayaan Masyarakat Miskin Terdampak Banjir Melalui Pendidikan Kecakan Hidup dan Teknologi Tepat Guna di Kelurahan Kademangan Kabupaten Bondowoso - Hadi, Sofyan; Mukaffan, Mukaffan (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Kademangan Village is one of the villages in Bondowoso Regency which is geographically a densely populated lowland located in the center of Bondowoso City. This area is considered advanced because it directly borders the Bondowoso City sub-district, has road access which is a provincial road to Situbondo, Jember, and Banyuwangi regencies, and is a center of trade because in the village there are several educational institutions, hospitals, and government offices. The results of this study found that the empowerment of poor people who are victims of annual floods in Kademangan Village was carried out through several stages, namely posing the problem or identifying problems, analyzing problems, determining general and specific objectives, preparing detailed action plans, implementing activity programs, and evaluation. While the empowerment process is carried out through a series of activities in the form of preparing local cadre training programs, community assistance, waste bank management, procurement of public facilities to meet basic needs, and assistance for the community in the process of institutionalizing a democratic government system at the village level as a manifestation of regional autonomy. The life skills education provided varies, including self-awareness skills or personal skills, rational thinking skills, social skills or interpersonal skills, and vocational skills or often referred to as vocational skills are what will be further used in community empowerment because they are related to certain fields of work in the community. The manifestation of life skills education is seen in deliberation education, network development, and development of appropriate technology.